The Bedrock Surface of the Western Lake Ontario Region: Evidence of Reactivated Basement Structures? - Eyles, Nicholas; Boyce, Joseph; Mohajer, Arsalan (Géographie physique et Quaternaire, 1993)
ABSTRACTLower Paleozoic bedrock strata, in south-central Ontario and the adjacent part of New York State are covered by a thick (100m+) blanket of Pleistocene glacial and interglacial sediments. The form of the buried bedrock surface has been reconstructed from 70,000 waterwell boreholes that extend through the entire Pleistocene cover using GIS data processing techniques. The sub-drift bedrock surface shows linear channels that connect the basins of lakes Huron, Ontario and Erie and which form part of an ancestral mid-continent Great Lake drainage system prior to modification and infilling during successive Pleistocene glaciations. This relict drainage system is cut across Lower Paleozoic carbonates and elastics up to 500 m thick, but the position of several channels is aligned above terrane boundaries, faults and other deep-seated and poorly understood geophysical anomalies in underlying mid-Proterozoic Grenville basement rocks. Other channels are controlled by a dominant northwest and northeast trending regional joint system. A close relationship among deeply seated geophysical lineaments, basement structures and topographic lineaments cut across thick Paleozoic cover strata suggests a history of Phanerozoic reactivation and upward propagation of fractures from the Precambrian basement. Several basement structures and lineaments are seismically active suggesting ongoing neotectonic activity across the 'stable' craton of south-central Ontario.